David and goliath ebook Underdogs, misfits, and the art of battling giants. - Gladwell, Malcolm (2013)
Explore the power of the underdog in Malcolm Gladwell's dazzling examination of success, motivation, and the role of adversity in shaping our lives, from the bestselling author of  The Bomber Mafia . Three thousand years ago on a battlefield in ancient Palestine, a shepherd boy felled a mighty warrior with nothing more than a stone and a sling, and ever since then the names of David and Goliath have stood for battles between underdogs and giants. David's victory was improbable and miraculous. He shouldn't have won. Or should he have? In David and Goliath , Malcolm Gladwell challenges how we think about obstacles and disadvantages, offering a new interpretation of what it means to be discriminated against, or cope with a disability, or lose a parent, or attend a mediocre school, or suffer from any number of other apparent setbacks. Gladwell begins with the real story of what happened between the giant and the shepherd boy those many years ago. From there, David and Goliath examines Northern Ireland's Troubles, the minds of cancer researchers and civil rights leaders, murder and the high costs of revenge, and the dynamics of successful and unsuccessful classrooms—all to demonstrate how much of what is beautiful and important in the world arises from what looks like suffering and adversity. In the tradition of Gladwell's previous bestsellers— The Tipping Point , Blink , Outliers and What the Dog Saw — David and Goliath draws upon history, psychology, and powerful storytelling to reshape the way we think of the world around us.